2015
DOI: 10.1177/0148558x15617396
|View full text |Cite
|
Sign up to set email alerts
|

Auditor Pricing of Excess Cash Holdings

Abstract: We examine auditor business risk by analyzing the relation between excess cash holdings and auditor pricing behavior. Prior research links excess cash holdings to risks associated with manager opportunism and external monitoring. Our analyses provide evidence of a positive relationship between excess cash and audit fees. The economic magnitude of the increase in total audit fees due to an increase in excess cash holdings is approximately 5% greater for firms in the top quartile of excess cash holdings versus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 82 publications
3
27
0
Order By: Relevance
“…Kedia and Philippon (2009) suggest a theory of managerial optimism—managers have a primary desire for consistent over‐investment, and earnings manipulation is necessary. Gleason, Greiner, and Kannan (2017) argue that excess cash holdings are positively associated with audit fees because they are necessary for CEOs to overinvest and they reflect agency costs and business risks. Benmelech, Kandel, and Veronesi (2010) consider the information environment and show that compensation schemes affect managers’ risk policies and investment decisions.…”
Section: Additional Testsmentioning
confidence: 99%
“…Kedia and Philippon (2009) suggest a theory of managerial optimism—managers have a primary desire for consistent over‐investment, and earnings manipulation is necessary. Gleason, Greiner, and Kannan (2017) argue that excess cash holdings are positively associated with audit fees because they are necessary for CEOs to overinvest and they reflect agency costs and business risks. Benmelech, Kandel, and Veronesi (2010) consider the information environment and show that compensation schemes affect managers’ risk policies and investment decisions.…”
Section: Additional Testsmentioning
confidence: 99%
“…Regarding the impact of cash holding held in Egyptian listed firms on the audit fees, the results showed that the first hypothesis is accepted which means that cash holding increase audit fees due to the auditor's concern about the cash holding as a result auditor imposes additional audit costs. Gleason et al (2015) argued that agency's conflicts over the cash holding may increase the risk of litigation and damage to reputation. This result consistent with the agency theory, which some managers seek to maintain their personal power and interests, and therefore the auditors consider these as the highest risk and increase the audit fees.…”
Section: Resultsmentioning
confidence: 99%
“…This was justified on the basis that having an independent board ensures cash holdings to be appropriately invested, and thus lower both audit risks and audit fees. Gleason et al (2015) investigated the relationship between cash holdings and audit fees, applied to a sample of publicly U.S. firms provided by Standard and Poor's database, which amounted to 14576 firm-year observations, from 2002-2010, the study found a positive relationship between cash holdings and audit fees, but audit fees decline among clients who hold cash assets and have greater investment opportunities-the allocation of that assets appropriately-than those firms that tend to just hold those assets (holding those assets is just reserves), suggesting that auditors are less worried about the risks when managers have opportunities to distribute funds towards investments of positive Net Present Value (NPV), while audit fees increase in the firms that have cash holdings and implemented corporate governance mechanisms because shareholders in such firms may be more willing to challenge management through proxy fights or civil litigation, thus audit fees decline in the firms with weak governance in return.…”
Section: The Impact Of Corporate Governance Mechanisms On the Relatiomentioning
confidence: 99%
See 1 more Smart Citation
“…(3) applying domestic resources in new projects and investments without financing from external creditors and markets, known as a speculative motive (Gleason et al, 2017).…”
Section: Introductionmentioning
confidence: 99%